Generation of femtosecond laser pulses at 396 nm in K3B6O10Cl crystal - 张宁华 滕浩 黄杭东 田文龙 朱江峰 吴红萍 潘世烈 方少波 魏志义 (中国物理B：英文版, 2016)
K3B6O10Cl （KBOC）, a new nonlinear optical crystal, shows potential advantages for the generation of deep ultraviolet （UV） light compared with other borate crystals. In this paper we study for the first time the second harmonic generation （SHG） of a femtosecond Ti：sapphire amplifier with this crystal. Laser power is obtained to be as high as 220 mW at the central wavelength of 396 nm with a 1-mm-long crystal, and the maximum SHG conversion efficiency reaches 39.3%. The typical pulse duration is 83 fs, The results show that second harmonic （SH） conversion efficiency has the room to be further improved and that the new nonlinear crystal is very suited to generate the high efficiency deep ultraviolet laser radiation below 266 nm.